Factors Contributing Pre-service English Teacher Speaking Anxiety - Fuadiyah, Wilda; Yunita, Indah Nur; Suryaman, Maman (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This study focuses on what are the levels of speaking anxiety experienced by pre-service English teacher. The data was collected from Foreign Language Classroom Anxiety Scale questionnaire developed by Horwitz et al. (1986) through Google Form provided to 22 English language education students. It has 33 items on a 5-point Likert scale. Using Oetting scale, the data that has been collected will be categorized and then interpreted. The results of this research show that more than half of the students in this study have moderate anxiety, severe anxiety, or mild anxiety.